Fleksibilitas dan burnout karyawan pasca pandemi COVID-19: Menguji peran mediasi keseimbangan kehidupan kerja: Employee flexibility and burnout post COVID-19 pandemic: Testing the mediating role of work-life balance - Setyaningsih, Sekar Hayu; Satwika, Pratista Arya (Persona:Jurnal Psikologi Indonesia, 2024)
The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives. The transition of work systems from WFH to WFO to establish the new normal after COVID-19 has led to excessive workload, resulting in prolonged fatigue and stress symptoms for employees. This research aims to examine the influence of work-life balance as a mediator in the influence between flexibility and employee burnout. The measurement tools used in this study are the burnout scale (α=0.970), flexibility scale (α=0.82), and work-life balance scale (α=0.973). This research employs a quantitative method with participants consisting of employees working in Jakarta. Involving 104 research participants, this study utilizes a non-probability sampling technique with convenient online sampling. The research data is analyzed using the Process Macro for SPSS 3.0 by Hayes (2018). The results of this study state that flexibility and employee burnout are significantly affected by work-life balance. The implications of this study indicate that work-life balance plays an important role in the relationship between flexibility and burnout. Efforts to reduce employee burnout can be made by developing intervention programs related to understanding and skills in balancing employees' work lives.